Overview of Nasal Soft Tissue Reconstruction: Keeping It Simple - Weathers, William M.; Koshy, John C.; Wolfswinkel, Erik M.; Thornton, James F. (Seminars in Plastic Surgery, 2013)
The authors provide an overview of nasal soft tissue reconstruction and of the senior author's practice. Nasal soft tissue reconstruction is a challenging endeavor as the nose is one of the most prominent and complex facial features. A multitude of surgical repair options exist, which can make the decision-making process unnecessarily complicated. It is advisable that the reconstructive surgeon become facile with a handful of surgical techniques versus trying to master many techniques.
Keywords: nasal reconstruction; Mohs surgery; forehead flap; nasolabial flap; dorsonasal flap; secondary intention; full-thickness skin graft